2022
DOI: 10.3389/fphar.2022.840478
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Antihypertensive and Cardioprotective Potentials of Hot and Cold Aqueous Extracts of Hibiscus sabdariffa L. in Relation to Their Metabolic Profiles

Abstract: Ethnopharmacological relevance: Since ancient times, Hibiscus sabdariffa L. calyces have been used as a folk remedy for the treatment of hypertension. However, it is questionable as to whether there is a difference in the antihypertensive activity of the hot or cold aqueous extracts.Aim of the study: We designed this study to specify the best method for water extraction of the antihypertensive metabolites of H. sabdariffa and to confirm their in vivo antihypertensive capabilities.Materials and methods: The pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
(69 reference statements)
0
4
0
4
Order By: Relevance
“…Several antihypertensive mechanisms are linked to the actions of HS. HS could exert diuretic and vasodilating activities, and inhibition of angiotensin converting enzyme ( Salem et al, 2022 ). Our data reported the influence of HS on controlling arterial blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Several antihypertensive mechanisms are linked to the actions of HS. HS could exert diuretic and vasodilating activities, and inhibition of angiotensin converting enzyme ( Salem et al, 2022 ). Our data reported the influence of HS on controlling arterial blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…But, the relevance of in vitro ACE inhibition seems more difficult to extrapolate to the in vivo situation. However, the physiological effects of ACE inhibition on hypertension can be inferred from the high values of bioaccessibility and bioavailability of phenolic compounds as well as from in vivo ACE inhibition results of them that have been reported in the literature (Häckl et al, 2002; Kasprzak‐Drozd et al, 2021; Salem et al, 2022). However, more research is needed in the future to obtain information regarding the components of ingested functional foods or functional food ingredients that will reach ACE in serum, lungs, and kidneys to inhibit it and thus reduce blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…PL was prepared by heat treatment with water. It has been reported that heat treatment with water leads to extraction of more amount of total phenolics which might have contributed to the cytotoxicity observed with PL [ 23 ]. The study revealed among the four formulations, silver nanoparticles based on PLE (PNP) and Papaya extract prepared using a SF extraction machine (PE) showed activity against DENV -2 virus under all conditions though the effect was more pronounced in post infection treatment conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic effect of papaya formulations (commercial and plant material formulations) on Vero CCL-81 cells were evaluated using 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay [ 23 ]. Briefly, Vero cells were incubated with different concentrations of test formulations (0–200 μg/ml) at 37°C for 5 days.…”
Section: Methodsmentioning
confidence: 99%